PENGARUH ABU SEKAM PADI DAN BEBERAPA JENIS PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG ( Zea mays saccharata Sturt . ) DI LAHAN GAMBUT - Normaida Nainggolan; Jurnawaty Sjofjan; Edison Anom (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to determine the interaction effect of rice husk ash and some types of manure on the growth and production of sweet corn and get a dose of the best in peat. Research has been carried out from June to September 2015 in the experimental field of the Faculty of Agriculture, University of Riau, Village Rimbo Panjang, Pekanbaru. The study was conducted using a factorial randomized block design consisting of two factors and three replications. The first factor is the rice husk ash (A), which consists of 4 levels, namely A1: 1.5 kg/plot (2.5 ton/ha), A2: 3 kg/plot (5 ton/ha), A3: 4.5 kg/plot (7.5 ton/ha), A4: 6 kg/plot (10 ton/ha) and the second factor is the manure (P) consisting of three types, namely P1: manure chicken, P2: manure goat and P3: cow manure. Parameters measured were the relative growth rate, leaf area, the ratio of crown roots, plant dry weight, while the male flowers appear, the time appears the female flowers, harvest, heavy perplot cob, cob without husk length, diameter and weight cob cob without husk. The results showed giving 7.5 ton/ha asp and chicken manure showed results highest production ie 9.93 kg/plot (16.55 ton/ha) Keywords: sweet corn, rice husk ash, manure, peat